Kisah Nuh Dan Terjadinya Air Bah Di Bumi: Tindakan Kasih Karunia Allah Berdasarkan Kejadian 6-9 - Erikson Pane; Rudolf Weindra Sagala; Exson Pane; Janes Sinaga (Sekolah Tinggi Teologi Arastamar Bengkulu, 2022)
The purpose of the study is for everyone to understand the meaning of why God sent down the flood in the days of Noah's life, so that everyone can live righteously in this day and age. The story of Noah and the occurrence of the flood is to tell how God saved life on earth when the people who lived in it grew evil from time to time. God told Noah to build the Ark according to the details that God gave as a means of salvation when the flood destroyed life on earth. The flood was God's way of reconstructing the earth and life on it without re-creating, by saving Noah and his family as pious people at that time. This research was conducted with a qualitative method by collecting data from various bibliography such as Bibles, books and journal manuscripts. Through this research, it is hoped that everyone will understand God's love and plan for His people, even in the event of a disaster.